Televizyonunun kültür üzerindeki etkileri - Demirci, Ömür (My University, 1999)
THE EFFECTS OF TELEVISION ON CULTURE Mass Communication Means shape mass culture against the national values of the society, this new mentality changes the value judgements of the society being under the effect of mass communication means. The most effective one among mass communication means is television. Television has its own interpretation world. It presents topics in the form of drama. Everything in broadcasting is presented to audiences by passing from the interpretation process of television. After the analysis of these influences of TV, it is necessary to evaluate which cultural elements are being used most. Television uses the mass culture addressing to everyone. It produces the fashion concepts that are on the agenda. We have examined how the nature of TV, peculiar to itself, effects the society in the frame of social institutions consisting the society in the sociological aspect. The one that is most influenced by TV is family. Acceptation of TV as an entertaining instrument makes family pass time in front of TV as individuals who are separated from each other, but in a same place. The one most effected by TV in the family is child. The most important instrument in the socialisation of the child is television. Television supports the system unless its own mentality conflicts with the existing political system. The main reason for using TV as a politics instrument stems from its success in directing public opinion. Television has made essential impacts on the education system. Especially, there exists a mentality dominated by mainly written culture. First education was provided by elder members of family. Television is taking the place of this conventional education understanding. In other words, television takes the role of elder members of family. Television has an economic mentality inciting the consumption. The use-throw understanding ruling the mass culture is the mentality used by TV. The audience considers TV as an entertaining instrument is in the passive position in front of TV. TELEVİZYONUN KÜLTÜR ÜZERİNDEKİ ETKİLERİ Kitle iletişim araçları, toplumun milli değerlerine karşı kitle kültürünü işlerler bu yeni anlayış kitle iletişim araçlarının etkisi altındaki toplumun kendi değer yargılarını değiştirir. Kitle iletişim araçları içinde en etkili olana televizyondur televizyonun kendi-ne has anlamlandırma dünyası vardır. Konuları izleyiciye bir drama biçiminde sunar Yayına giren herşey televizyonun anlamlandırma sürecinde geçerek izleyiciye sunar. Televizyonun bu etkilerinin tahlilinden sonra ağırlıklı olarak hangi kültür unsurlarını kullandığına bakmak lazımdır. Televizyon herkese hitap eden kitlesel kültürü kullanır. Gündemde olan moda kavramlar üretir. Televizyonun kendine has doğasının toplumu nasıl etkilediğini sosyolojik açıdan toplumu oluşturan sosyal kurumlar çerçevesinde araştırdık. Televizyondan ençok etki-lenen ailedir. Televizyonun bir eğlence aracı olarak görülmesi ailenin televizyon karşı-sında birbirinden kopup ama aynı mekanı paylaşan bireyler olarak vakit geçirmelerini sebep olmaktadır. Aile içinde televizyondan ençok etkilenen çocuktur. Çocuğun sos-yalleşmesinde en önemli araç televizyondur. Televizyon varolan siyasi sistem kendi anlayışı ile çatışmadığı sürece, sistemi destekler. Televizyonun siyasi bir araç olarak kullanılmasının en önemli sebebi televiz-yonun kamu oyunu yönlendirmedeki başarısından kaynaklanmaktadır. Televizyon eğitim sistemi üzerinde de önemli etkiler yapmıştır. Özellikle yazıya dayalı kültürün hakim olduğu bir anlayış vardır. İlk eğitim ailenin büyükleri tarafından verilirdi. Bu geleneksel eğitim anlayışının yerini televizyon almaktadır. Televizyon ai-lenin büyüklerinin rolünü üstlenmektedir. Televizyon tüketimi pompalayan bir ekonomik zihniyete sahiptir. Kitle kültürün-de hakim olan kullan-at anlayışı televizyonun kullandığı ekonomik zihniyettir. tele-vizyonu eğlence aracı olarak gören izleyici televizyon karşısında pasif bir durumdadır.
Keywords: Televizyon_Türkiye